Lata 70. – fragmenty mozaiki - Maga, Anna (Człowiek i Społeczeństwo, 2017)
Anna Maga, Lata 70. – fragmenty mozaiki [The 70s – Fragments of the mosaic], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 31-62, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. Design is a creative area which is deeply dependent on material conditions: on technological and productive capacity and on production management. Polish design in the 70s was significantly influenced by political changes and new strategy of economic development based on the money borrowed from western countries. Thanks to foreign licenses producers and designers gained bigger technological potential. At the same time a lot of interesting works were created due to the activity of previously established institutions: design centres in factories and in the unions of particular industries. The article attempts to point out discrepancies between the advanced system of organisation and promotion of design and the real professional practice of designers. As it is really difficult to prepare an objective and synthetic view on the decade, the author relates her interviews with some of designers who were active in Poland in the 70s. As a result the reader becomes aware of what designing and producing was really like at that time in the sectors of electro-acoustic equipment, furniture, glass, fashion. The author also gives some important examples of projects realized in the serial production.